Efektivitas Strategi Card Sort dalam Pembelajaran IPA pada Siswa Kelas IV SD Muhammadiyah 10 Palembang - Piko Priando; Dian Nuzulia Armariena; Rury Rizhardi (Departement of Mathematics Education, 2023)
This research is motivated by the fact that the application of this material has not been fully maximized and optimal, especially in science learning. And also students still have a lot of difficulties understanding learning material and solving problems a given problem, because in teaching and learning activities the teacher only uses direct learning (lectures) and is only fixated on textbooks. This study aims to determine the effectiveness of the card sort strategy in learning science in class IV SD Muhammadiyah 10 Palembang. In this study using experimental research methods. Experimental research